The Effect of Compensation on Turnover Intention Mediated by Job Satisfaction of Employees of PT Bumi Asri Nusa - Fauzan, Muh Aghil; Haeruddin, Muhammad Ilham Wardhana; Dipoatmodjo, Tenri Sayu Puspitaningsih; Ruma, Zainal; Hamka, Rezky Amalia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to measure the impact of compensation on turnover intention mediated by job satisfaction of PT Bumi Asri Nusa employees. This research uses quantitative methods with a descriptive approach. The population in this study were all employees of PT Bumi Asri Nusa. Sampling was done using purposive sampling. The method used in this research is Structural Equation Modeling (SEM) with the support of Smart PLS 4.0 software. The data analysis process includes validity testing, reliability testing, and structural model testing. The results showed that: (1) compensation has a negative and significant effect on turnover intention at PT Bumi Asri Nusa. (2) compensation has a positive and significant effect on employee job satisfaction at PT Bumi Asri Nusa. (3) job satisfaction has a negative and significant effect on turnover intention at PT. Bumi Asri Nusa. (4) job satisfaction has a negative and significant effect in mediating the effect of compensation on turnover intention.